Development of a prediction model for bacteremia in hospitalized adults with cellulitis to aid in the efficient use of blood cultures: a retrospective cohort study. Issue 1 (December 2016) - Lee, Chun-Yuan; Kunin, Calvin; Chang, Chung; Lee, Susan; Chen, Yao-Shen; Tsai, Hung-Chin
Abstract Background Cellulitis is a common infectious disease. Although blood culture is frequently used in the diagnosis and subsequent treatment of cellulitis, it is a contentious diagnostic test. To help clinicians determine which patients should undergo blood culture for the management of cellulitis, a diagnostic scoring system referred to as the Bacteremia Score of Cellulitis was developed. Methods Univariable and multivariable logistic regression analyses were performed as part of a retrospective cohort study of all adults diagnosed with cellulitis in a tertiary teaching hospital in Taiwan in 2013. Patients who underwent blood culture were used to develop a diagnostic prediction model where the main outcome measures were true bacteremia in cellulitis cases. Area under the receiver operating characteristics curve (AUC) was used to demonstrate the predictive power of the model, and bootstrapping was then used to validate the performance. Results Three hundred fifty one cases with cellulitis who underwent blood culture were enrolled. The overall prevalence of true bacteremia was 33/351 cases (9.4 %). Multivariable logistic regression analysis showed optimal diagnostic discrimination for the combination of age ≥65 years (odds ratio [OR] = 3.9; 95 % confidence interval (CI), 1.5–10.1), involvement of non-lower extremities (OR = 4.0; 95 % CI, 1.5–10.6), liver cirrhosis (OR = 6.8; 95 % CI, 1.8–25.3), and systemic inflammatory response syndrome (SIRS) (OR = 15.2; 95 % CI, 4.8–48.0). These four independent factors were included in the initial formula, and the AUC for this combination of factors was 0.867 (95 % CI, 0.806–0.928). The rounded formula was 1 × (age ≥65 years) + 1.5 × (involvement of non-lower extremities) + 2 × (liver cirrhosis) + 2.5 × (SIRS). The overall prevalence of true bacteremia (9.4 %) in this study could be lowered to 1.0 % (low risk group, score ≤1.5) or raised to 14.7 % (medium risk group, score 2–3.5) and 41.2 % (high risk group, score ≥4.0), depending on different clinical scores. Conclusions Determining the risk of bacteremia in patients with cellulitis will allow a more efficient use of blood cultures in the diagnosis and treatment of this condition. External validation of this preliminary scoring system in future trials is needed to optimize the test.